Signifikansi Pemilihan Kata Tijārah dalam Q.S. Aṣ-Ṣaff [61]: 10-11 (Studi Analisis Hermeneutika Ma’nā-Cum-Maghzā) - Ahmed Zaranggi Ar Ridho (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2022)
This article examines the main message (maghzā) of the choice of the word tijārah in Q.S Aṣ-Ṣaff (61): 10-11. Armed with an understanding that the Qur'an did not come down in a vacuum, its verses will respond to the conditions of Arab society at the time of revelation. Commerce is the livelihood of the Arab community, especially the residents of the city of Mecca. For this reason, the issue of commerce cannot be separated from the context of the revelation of the Qur'an. Commerce in Arabic is defined as tijārah, this word can then be used as the key to see how the Qur'an responds to Arab commerce and provides guidance through it. To find the significance of the use of the word tijārah in the verse, this study uses a ma'nā-cum-maghzā hermeneutic approach. A balanced interpretation method that combines text and context, as well as the past and the present to produce a contextual interpretation. As a result, the use of the word tijārah in this verse is not without meaning, but contains two main messages. First, the shift in perspective (worldview); namely from commerce that is quantitative-material (worldly) to non-material-qualitative (spiritual) commerce. Second, the command to carry out meaningful commerce in totality; namely by strengthening faith in Allah and the Messenger of Allah and fighting in the way of Allah with all his wealth and body and soul.